Potential molecular targets of statins in the prevention of hepatocarcinogenesis - Ridruejo, Ezequiel (2017)
Introduction and aim. Hepatocellular carcinoma (HCC) represents 90% of liver tumors. Statins, may reduce the incidence of various tumors, including HCC. Antitumoral activities may be mediated by changes in transforming growth factor-beta (TGF-β1) and thyroid hormones (TH) regulation. Aim. The aim of our study is to establish the statins mechanism of action and the potential key molecules involved in an in vivo and in vitro HCC model. Materials and methods. We used two models: in vivo (in rats) using di-ethylnitrosamine (DEN) and hexachlorobenzene (HCB) to develop HCC. We analyzed cell proliferation parameters (proliferating cell nuclear antigen, PCNA) and cholesterol metabolism (hydroxy-methylglutaryl-CoA reductase, HMGCoAR). In vitro (Hep-G2 cells) we evaluated the effects of different doses of Atorvastatin (AT) and Simvastatin (SM) on HCB induced proliferation and analyzed proliferative parameters, cholesterol metabolism, TGF-β1 mRNA, c-Src and TH levels. Results. In vivo, we observed that cell proliferation significantly increased as well as cholesterol serum levels in rats treated with HCB. In vitro, we observed the same results on PCNA as in vivo. The statins prevented the increase in HMG-CoAR mRNA levels induced by HCB, reaching levels similar to controls at maximum doses: AT (30 μM), and SM (20 μM). Increases in PCNA, TGF-β1, and pc-Src, and decreases in deiodinase I mRNA levels induced by HCB were not observed when cells were pre-treated with AT and SM at maximum doses. Conclusion. Statins can prevent the proliferative HCB effects on Hep-G2 cells. TGF-β1, c-Src and TH may be the statins molecular targets in hepatocarcinogenesis.